Pengukuran Gula Darah Mandiri Sebagai Langkah Deteksi Dini Diabetes Pada Usia Produktif di Perumahan Griya Putri Ayu Blok T1 Talang Kelapa - Agnes Felicia Lubis; Yudistira Putra (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Blood glucose levels are something that the general population is aware of and should be tested on a regular basis. These regular checks can help to prevent a rise in diabetes, which has the potential to limit productivity; thus, it is critical to know the level of glucose in the community. Griya Putri Ayu Housing Block T1 to better comprehend the implications. The goal Community service is done out to raise awareness and information about the importance of regulating blood sugar levels in Griya Putri Ayu Housing Society Block T1, Alang-alang Lebar District, Palembang City. Method: Community service is done out by monitoring blood sugar levels using an autochek. The blood sugar levels of 11 participant were examined. The average blood sugar level of Griya Putri Ayu Housing Block T1 occupants is 108.4 mg/dl, with 1 person having diabetes mellitus because blood glucose levels surpass the normal limit of 250 mg/dLDiscussion: Following screening, residents are found to be better educated about blood glucose levels. It is believed that by doing so, Griya Putri Ayu Housing Block T1, Alang-alang Lebar District, Palembang City residents would become more conscious of the need of leading a healthier lifestyle.